اتجاهات الطلبة نحو التحاقهم بتخصص المحاسبة في ليبيا دراسة حالة على قسم المحاسبة جامعة سرت (Economic studies journal, 2022)
The study aimed to identify the social, academic and economic trends of students at the University of Sirte towards their enrollment in the accounting major, from the point of view of the students of the Accounting Department. A questionnaire, and distributed to the students, who numbered (42) students.The study used the statistical program (SPSS) to conduct the necessary tests to ensure the suitability of the study data for statistical analysis and to test the hypotheses of the study, including the T-Test for one sample. They joined the accounting major, and the economic trend came first in terms of students' trends, in terms of relative importance and the social trend in the last order. In light of the results, the study recommended, with regard to the social trend, to increase the activation of the role of the accounting profession in society through the public sector, the private sector, and the Libyan Accountants and Auditors Syndicate, so that they parallel the professions of medicine, engineering and law. And activating the role of academic guidance and counseling in the departments. With regard to the economic trend, the study recommended a review of the financial compensation for accountancy practitioners, whether in the public sector or the private sector.
Keywords: Trends; Accounting Specialty; University of Sirte; Libya